Implementation strategy of primary health care in Ovia communities - Osarenmwanta Aideyan Daniel; Timothy A Akingbade; Mohamed Nor Azhari Azman; Jems K.R. Maay (Intelektual Pustaka Media Utama, 2021)
Primary health care is the essential health service provided at the grassroot level. Over the years the implementation of Primary Health Care (PHC) programmes in Edo state are bedeviled with associated challenges such as limited community participation, great communication gap that limit evaluation processes of PHC programme and slow pace collaboration among stakeholders. These challenges need to be averted through effective and people oriented strategies to ensure the implementation of primary health care. A descriptive research design with a population of the study comprised 1,024 primary health care stakeholders in Edo state. Multi-stage sampling technique was used to select 180 respondents for the study. The study found that intersectoral collaboration involving partnerships with community health agencies such as village health committees and ward health committees significantly influenced the implementation of PHC. Intersectoral collaboration, community mobilization strategy and community feedback mechanism are effective and efficient strategies for improved implementation of PHC programmes. The study recommended among others that National Primary Health Care Development Agency (NPHCDA) and State Primary Health Care Development Agency (SPHCDA) should strengthen partnership with international health organizations such as WHO, UNICEF, GAVI, UNDP and boost confidence and trust of these international organizations.